2018
DOI: 10.1016/j.redox.2017.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotection of CAPE-oNO2 against myocardial ischemia/reperfusion induced ROS generation via regulating the SIRT1/eNOS/NF-κB pathway in vivo and in vitro

Abstract: Caffeic acid phenethyl ester (CAPE) could ameliorate myocardial ischemia/reperfusion injury (MIRI) by various mechanisms, but there hadn’t been any reports on that CAPE could regulate silent information regulator 1 (SIRT1) and endothelial nitric oxide synthase (eNOS) to exert cardioprotective effect. The present study aimed to investigate the cardioprotective potential of caffeic acid o-nitro phenethyl ester (CAPE-oNO2) on MIRI and the possible mechanism based on the positive control of CAPE. The SD rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 46 publications
3
107
0
2
Order By: Relevance
“…From the results we obtained, NaF toxicity upregulated both NF‐κB and Nrf2 indicating the capacity of NaF to modulate signaling associated with inflammation, oxidative stress and antioxidant response elements (ARE). Oxidative stress has been reported to be a major trigger of NF‐κB signaling . The observed upregulation of Nrf2 was also a confirmation of the significant increase in the activities of renal GRed, GPx, CAT, and SOD in NaF alone signifying adaptive response of these antioxidant enzymes through Nrf2/ARE pathway to NaF toxicity.…”
Section: Discussionsupporting
confidence: 61%
“…From the results we obtained, NaF toxicity upregulated both NF‐κB and Nrf2 indicating the capacity of NaF to modulate signaling associated with inflammation, oxidative stress and antioxidant response elements (ARE). Oxidative stress has been reported to be a major trigger of NF‐κB signaling . The observed upregulation of Nrf2 was also a confirmation of the significant increase in the activities of renal GRed, GPx, CAT, and SOD in NaF alone signifying adaptive response of these antioxidant enzymes through Nrf2/ARE pathway to NaF toxicity.…”
Section: Discussionsupporting
confidence: 61%
“…46 Recent studies demonstrated that NF-κB has cardioprotective effects though repression of apoptotic cell death induced by hypoxia or myocardial injury. [47][48][49] F I G U R E 5 Role of NF-κB in the protective effect of chlorogenic acid against TNF-α injured cardiomyocytes. hiPSC-CMs were treated with QNZ (1 nmol/L) for 4 h or CGA (0.1 μmol/L or 1 μmol/L) for 12 h prior to incubation with TNF-α for 24 h. Then the apoptosis rate of hiPSC-CMs was detected by Annexin V/PI staining, and the quantitative analysis of hiPSC-CMs apoptosis rate is shown (A, B).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Studies identified various molecular and cellular mechanisms involved in the process of myocardial I/R. [3][4][5][6][7] Of these, intracellular calcium [Ca 2+ ]i overload is a critical one that leads to cardiomyocyte apoptosis and cell death. [8][9][10] Dexmedetomidine (DEX) is a highly selective α2-adrenoceptor agonist with sedative, anxiolytic, analgesic, and sympatholytic properties.…”
Section: Introductionmentioning
confidence: 99%